Is Leader–Member Exchange Differentiation Beneficial or Detrimental for Group Effectiveness? A Meta-Analytic Investigation and Theoretical Integration - Yu, Andrew; Matta, Fadel K.; Cornfield, Bryan (Academy of Management Journal, 2018)
Despite the burgeoning number of studies that have examined leader-member exchange (LMX) differentiation, definitive conclusions regarding its effects remain scarce. We propose a theoretical framework for studying LMX differentiation through an equity-equality perspective derived from allocation preferences theory, allowing us to elucidate both the beneficial and detrimental influences LMX differentiation can have on workgroups. In a meta-analytic investigation including 4,114 workgroups and 21,745 individuals, we found that LMX differentiation was detrimental to collective harmony and solidarity, as indicated by a consistent negative relationship with emergent states and group processes. A theoretical integration of our predictions within an input-mediator-outcome model of group effectiveness revealed a more complex pattern of relationships with group performance. By simultaneously considering the proximal and distal nature of group outcomes, we found that emergent states and group processes not only mediated the negative indirect relationship, but also suppressed the positive direct relationship between LMX differentiation and group performance. These findings demonstrate the utility of an equity-equality framework for understanding LMX differentiation in workgroups and imply that there are tradeoffs associated with differentiation that must be considered when predicting group effectiveness criteria.